![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) -152 - (3x + 1) = (-2).(-3)3
-152 - 3x - 1 = (-2).(-27)
-3x - 153 = 54
-3x = 54 + 153
-3x = 207
x = -69
b) x - 43 = (35 - x) - 48
x - 43 = 35 - x - 48
x - 43= -x - 13
x = -x - 13 + 43
x = 30 + x
x + x = 30
2x = 30
x = 15
![](https://rs.olm.vn/images/avt/0.png?1311)
1/ \(2.\left(-2\right)^3+5.\left(-6\right)-\left(-26\right)\)
\(=2.8+\left(-30\right)-\left(-26\right)\)
\(=16+\left(-30\right)-\left(-26\right)\)
\(=-14-\left(-26\right)\)
\(=12\)
2/ \(\left(-12\right)+\left(17-x\right)=6\)
\(17-x=6-\left(-12\right)\)
\(17-x=18\)
\(x=17-18=-1\)
3/ \(\left(x-1\right)^2=4\)
\(\Rightarrow\left(x-1\right)^2=2^2\)
\(\Rightarrow x-1=2\)
\(\Rightarrow x=3\)
Chúc bạn học tốt nha
2.(-2)^3+5.(-6)-(-26)=2.(-8)+5.(-6)-(-26)=(-16)+(-30)-(-26)=-20
-12+(17-x)=6
17-x=6-(-12)
17-x=18
x=17-18
x=-1
(x-1)^2=4
=>x-1=2
x=2+1
x=3
57.(43-14)-43.(57+14)=57.29-43.71=1653-3053=-1400
![](https://rs.olm.vn/images/avt/0.png?1311)
tìm số ngyên x :
a) -2x-(x-17)=34-(-x+25)
-2x - x +17 =34 + x -25
-3x + 17 =9 +x
-3x + 17 - 9 -x=0
-4x + 8 = 0
-4x = -8
x =2
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(12\left(2x-6\right)-43=5^3\)
\(12\left(2x-6\right)=125+43\)
\(12\left(2x-6\right)=168\)
\(\left(2x-6\right)=168:12\)
\(\left(2x-6\right)=14\)
\(2x=14+6\)
\(2x=20\)
\(x=20:2\)
\(x=10.\)
b) \(7\left(25-3x\right)=3^4-2^5\)
\(7\left(25-3x\right)=49:7\)
\(7\left(25-3x\right)=7\)
\(\left(25-3x\right)=7:7\)
\(\left(25-3x\right)=1\)
\(3x=25-1\)
\(3x=24\)
\(x=24:3\)
\(x=8.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) -2x-x+17=34+x-25
<=> -2x-x-x=34-25-17
<=> -4x=-8
<=> x=2
b)17x+16x+37=2x+43
<=> 33x-2x=43-37
<=> 31x=6
<=>x=\(\frac{6}{31}\)
c) -2x-3x+51=34+2x-50
<=>-5x-2x=34-50-51
<=>-7x=-67
<=>x=\(\frac{67}{7}\)
d) [-2.(4x2-4x+1)- 1]=-106
<=> -8x2+8x-2-1=-106
<=>-8x2+8x=-103
43- 2x2= 14
=>2x2= 29
=>x2=29/2=\(\left(\sqrt{\frac{29}{2}}\right)^2\)
=>x=\(\sqrt{\frac{29}{2}}\)hoặc x=\(-\sqrt{\frac{29}{2}}\)